2015
DOI: 10.1007/s12038-015-9529-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensory cues employed for the acquisition of familiarity-dependent recognition of a shoal of conspecifics by climbing perch (Anabas testudineus Bloch)

Abstract: In this study we showed that a freshwater fish, the climbing perch (Anabas testudineus) is incapable of using chemical communication but employs visual cues to acquire familiarity and distinguish a familiar group of conspecifics from an unfamiliar one. Moreover, the isolation of olfactory signals from visual cues did not affect the recognition and preference for a familiar shoal in this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Tilapia was purchased from aquarium keepers and individuals of length 6.1 (± 2.8) cm were chosen for the experiments in this study. As some of our own earlier studies have indicated that familiarity with individual fish can influence shoaling decisions in this species (Binoy and Thomas 2006;Binoy et al 2015), the absence of tilapia in the sites, from which the study climbing perch was collected, and in neighbouring areas was ensured by interviewing the local fishermen.…”
Section: Study Species and Its Husbandrymentioning
confidence: 99%
See 4 more Smart Citations
“…Tilapia was purchased from aquarium keepers and individuals of length 6.1 (± 2.8) cm were chosen for the experiments in this study. As some of our own earlier studies have indicated that familiarity with individual fish can influence shoaling decisions in this species (Binoy and Thomas 2006;Binoy et al 2015), the absence of tilapia in the sites, from which the study climbing perch was collected, and in neighbouring areas was ensured by interviewing the local fishermen.…”
Section: Study Species and Its Husbandrymentioning
confidence: 99%
“…Shoal-choice experiments were conducted in an apparatus consisting of an aquarium (85 × 32 × 32 cm), divided into two side chambers (16 × 32 × 32 cm) and a central chamber (53 × 32 × 32 cm) with transparent Plexiglas sheets with perforations (Binoy et al 2015). Three sides of the aquarium were covered with black paper and water filled up to a height of 28 cm.…”
Section: Shoaling Decisions: Apparatus and General Proceduresmentioning
confidence: 99%
See 3 more Smart Citations